The open society in theory and practice - Germino, Dante; Beyme, Klaus von (Springer Netherlands, 1974)
1. Preliminary Reflections on the Open Society: Bergson, Popper, Voegelin -- 2. Political Obligation and the Open Society -- 3. Political Society and the Open Society: Bergsonian Views -- 4. The Open World and Culture Change: Sacred and Secular Trends -- 5. Visions and Explanations, Four Perspectives on Education and Work -- 6. Some Views of the Closed Society -- 7. Authoritarian Regimes — Developing Open Societies? -- 8. Liberalism and the Open Society -- 9. The Liberal Theory of the Open Society -- 10. Imperfect Legitimacy -- 11. The Revolt Against the Open Society and the Phenomenon of Delegitimization: The Case of the American New Left -- 12. Marxism and the Open Society -- 13. Ideology, Openness and Freedom -- 14. The Higher Reaches of the Lower Orders: A Critique of the Theories of B. F. Skinner -- 15. Psychiatric Responsibility in the Open Society -- 16. Neither Sticks Nor Stones -- 17. The Ecology of Openness.
Keywords: Aufsatzsammlung; Offene Gesellschaft